The social dimension and cohesion: Complementary or contradictory? - Angelos Kotios; Manfred Schäfers (Intereconomics, 1990)
It is again being argued that the low labour costs and social standards in countries on the periphery of the EC—Greece, Ireland, Portugal and Spain—jeopardise employment in the northern EC countries and the social safety net they have constructed. A common social policy harmonising employment and social standards to safeguard the social status quo is therefore being advocated. How valid is this argument? What consequences would the implementation of such a “social action programme” have for the economies on the periphery? How are the Community's objectives with regard to cohesion and social policy to be reconciled?
Keywords: 330; European Community